2009
DOI: 10.1007/s12551-009-0010-y
|View full text |Cite
|
Sign up to set email alerts
|

Structure and functions of profilins

Abstract: Profilins are small actin-binding proteins found in eukaryotes and certain viruses that are involved in cell development, cytokinesis, membrane trafficking, and cell motility. Originally identified as an actin sequestering/ binding protein, profilin has been involved in actin polymerization dynamics. It catalyzes the exchange of ADP/ATP in actin and increases the rate of polymerization. Profilins also interact with polyphosphoinositides (PPI) and proline-rich domains containing proteins. Through its interactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
74
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(75 citation statements)
references
References 90 publications
(93 reference statements)
1
74
0
Order By: Relevance
“…Our results showed expression changes in components of the cytoskeleton, such as NEFL, tubulin subunits, and INA. Furthermore, we observed downregulation of DPYSL2 and 3 and upregulation of PFN1, which may interfere with remodeling of the cytoskeleton during development, a requirement for axon guidance [52,53]. 14-3-3 protein epsilon, found to be downregulated by PS, plays an essential role in neuronal migration by interacting with NUDEL and DISC1 [54,55].…”
Section: Discussionmentioning
confidence: 99%
“…Our results showed expression changes in components of the cytoskeleton, such as NEFL, tubulin subunits, and INA. Furthermore, we observed downregulation of DPYSL2 and 3 and upregulation of PFN1, which may interfere with remodeling of the cytoskeleton during development, a requirement for axon guidance [52,53]. 14-3-3 protein epsilon, found to be downregulated by PS, plays an essential role in neuronal migration by interacting with NUDEL and DISC1 [54,55].…”
Section: Discussionmentioning
confidence: 99%
“…For example, profilin, a PI(4,5)P 2 -binding protein involved in cytoskeletal restructuring and dynamic actin turnover, can competitively inhibit phospholipase C-mediated hydrolysis of PI(4,5)P 2 when bound. 104,135 are transported to the outer leaflet via floppases. 5 In addition to these ATP-dependent enzymes, scramblases, which can mediate ATP-independent bi-directional movement of lipids across the membrane, are also involved in maintaining phospholipid asymmetry.…”
Section: Box 1 Phospholipids As Key Regulators Of Intracellular Procementioning
confidence: 99%
“…Radiography analyses of the structures of human profilin isoforms imply that the substitution of profilin-I S29 by Y29 in profilin-II participates in the higher affinity of profilin-II for proline-rich sequences (Nodelman et al, 1999). In spite of the similarity in the 3D structures of human profilin-I and -II, the surface characteristics, such as exposure of hydrophobic patches (Figure 2), and biochemical properties of each isoform are different (Krishnan & Moens, 2009). Fig.…”
Section: Structural Aspects Of Profilinmentioning
confidence: 98%
“…1). The profilin polypeptide consists of 100-131amino acids (Krishnan & Moens, 2009) and it is folded into a central -pleated sheet formed of 5-7 antiparallel -strands (Schlüter et al, 1997). On one side, this core is flanked by N-and C-terminal -helices, with both termini next to each other, and on the opposed side by an extra -helix attached to either additional -helix or a small -strand (Schlüter et al, 1997) (Figure. It has been reported that there are three groups of ligands characterize profilins: (1) G-actin and actin-related proteins Schutt et al, 1989;Tobacman et al, 1983) (2) polyphosphoinositides (Lassing & Lindberg, 1985) (3) poly-L-proline (PLP) with the exception of Vaccinia profilin (Kaiser et al, 1989;Lindberg et al, 1988;Tanaka & Shibata 1985), existing either as a peptide or as a sequence motif in particular proteins.…”
Section: Structural Aspects Of Profilinmentioning
confidence: 99%
See 1 more Smart Citation